Національний рівень організації людського простору: український контекст - Кисельов, Ю. (Історико-географічні дослідження в Україні, 2021)
Окреслено проблему рівнів організації людського простору. Наголошено на національному рівні просторової організації Ойкумени як особливому прикладі регіонального рівня. Обґрунтовано схему територіальної диференціації людського простору в Україні. Виділено геософічні регіони – чотири «країносвіти» та одинадцять «краєсвітів» – на території України, характеризованих певними особливостями ландшафтно-етнічної взаємодії. Ecumenism is characterized by the multilevel nature of its organization. In particular, there are five levels – space, global (planetary), regional, national, and local. The national level of organization of human space is a special manifestation of the regional, as the object of study is the state or ethnic territory. The modern territory of the Ukrainian state and the Ukrainian ethnic territory within the boundaries outlined by Stepan Rudnytskyi are clear manifestations of the organization of the Ecumenical Council at the national level. The territory of Ukraine is marked by an almost unique combination of landscapes in Europe. Being in different natural zones, the territory of Ukraine at the same time preserves the internal unity caused by the ethnic integrity of the population. The presence of a transitional forest-steppe strip creates a gradual nature of the transition from one zonal landscape to another. This is a prerequisite for the formation of a special «forest-steppe» spirit of geospace, which led to the emergence of the phenomenon of the Ukrainian landscape as a living environment of the ethnos. Peculiarities of ethnogenesis of Ukrainians in different natural regions are considered in this article. It is emphasized that the processes of ethnogenesis are accompanied by landscape-ethnic interaction, the result of which is the assertion of the spirit of landscapes. On the basis of the unity of spiritual sphere at the national level of the Ecumenical organization, such geosophical regions as «country worlds» and «regional education» were distinguished. There are four «country worlds» – Polissia, western Ukraine, Central-Eastern Ukraine and Black Sea Crimean. In each of the «country worlds» as the severity of internal diversity in the nature of landscape-ethnic interaction, two or more «landscape worlds» are identified.